Business Environment Institutions in Rural, Urban-Rural and Urban Municipalities in Poland as Subjects Supporting Development of Entrepreneurship - Agnieszka ŻOŁĄDKIEWICZ-KUZIOŁA (Communications of International Proceedings, 2020)
The present article strives to provide answers to the following research queries: (1) Within Polish municipalities, are there disproportions regarding the number and type of business environment institutions functioning on their territories? (2) Is there any, and if yes, what type of support is granted to business environment institutions by municipality? The article presents the results of the author's survey study which was conducted from September to December 2018. The research tool used was a survey questionnaire in electronic form which was sent directly via email to all 2478 municipalities in Poland. In the research, the division into rural, urban-rural and urban municipalities was taken into consideration. The results have shown that there are significant disproportions in the number of business environment institutions functioning in municipalities in Poland. The smallest saturation with business environment institutions was reported in rural municipalities whereas the largest in urban municipalities. Among researched institutions, the largest group in the case of rural and urban-rural municipalities were information centres while in the case of urban municipalities investor service centres. Rural municipalities provide support to business environment institutions mainly in the form of advisory service, urban-rural municipalities provide access to premises and urban municipalities offer financial support.
Keywords: Entrepreneurship; Business Environment Institutions; Support of Entrepreneurship; Municipalities.